THE MEANINGS OF FI`IL ṠULĀṠI MAZĪD IN SURAH AL-FATḤ (ṢARAF ANALYSIS STUDY) - Ainun Alfiyah Rustam; Susiawati; Ahmad Sirfi Fatoni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research aims to describe the form and the meaning of each fi`il ṡulāṡi mazīd in surah Al-Fatḥ. Fi`il ṡulāṡi mazīd is a fi`il that consists of three original letters and gets additional letters totaling one, two, and three letters. This type of research is qualitative research with a literature study research design. This research focuses on the material of fi`il ṡulāṡi mazīd in ṣaraf. The data in this research are in the form of words in the verse snippets of surah Al-Fatḥ. There are two sources of data used, namely primary data sources and secondary data sources. The data collection techniques in this research are reading techniques and documentation techniques. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. The results of this research indicate that there are 66 forms of fi`il ṡulāṡi mazīd in surah Al-Fatḥ spread over 23 verses and divided into several wazans, including 13 fi`il following the wazan فَعَّلَ, 6 fi`il following the wazan فَاعَلَ, 32 fi`il following the wazan أَفْعَلَ, 6 fi`il following the wazan تَفَعَّلَ, 5 fi`il following the wazan اِفْتَعَلَ, 2 fi`il following the wazan اِنْفَعَلَ, and 2 fi`il following the wazan اِسْتَفْعَلَ. Fi`il ṡulāṡi mazīd in Surah Al-Fatḥ not only varies in terms of form, but also contains various meanings according to the wazan of formation. These meanings include لِلتَّعْدِيَةِ, لِلتَّحَوُّلِ, “فَعَّلَ” لِمُطَاوَعَةِ, “فَعَلَ” لِمُطَاوَعَةِ, “أَفْعَلَ” لِمُطَاوَعَةِ, لِلْمُشَارَكَةِ بَيْنَ اثنَيْنِ, الْمُجَرَّد “فَعَلَ” لِمَعْنَى, لِطَلَبِ الْفِعْلِ, لِلدُّخُولِ فِي الشَّيْءِ, dan لِزِيَادَةِ الْمُبَالَغَةِ فِي الْمَعْنَى.